PENGEMBANGAN INTELLECTUAL CAPITAL DALAM MEMBANGUN KINERJA UMKM KOMUNITAS DIFABEL: (Studi Kasus Di Kabupaten Klaten) - Rachman, Arif Nugroho; Triyanto, Eko (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
In facing global business competition, it is necessary to improve performance and competitiveness not only through products quality and cost efficiency, but also the use of Intellectual Capital, which includes Human Capital, Structure Capital, and Relational Capital. Similar to companies in general, the implementation of Intellectual Capital will also have an impact on MSMEs. The object of this research is the UMKM owned by the Difabel Community in Klaten. The test results show that all Intellectual Capital variables consisting of Human Capital, Structure Capital, and Relational Capital have a significant effect on the performance of MSMEs.